The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22041931
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IGF/IGF-1R Signaling in Hepatocellular Carcinomas: Stemness-Related Properties and Drug Resistance

Abstract: Insulin-like Growth Factor (IGF)/IGF-1 Receptor (IGF-1R) signaling is known to regulate stem cell pluripotency and differentiation to trigger cell proliferation, organ development, and tissue regeneration during embryonic development. Unbalanced IGF/IGF-1R signaling can promote cancer cell proliferation and activate cancer reprogramming in tumor tissues, especially in the liver. Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death, with a high incidence and mortality rate in Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 256 publications
1
35
0
Order By: Relevance
“…However, the interplay between YAP and IGF signaling has remained uncertain in HCC sorafenib resistance. We previously illustrated that high expression of IGF-1R correlates with expression of cancer stemness markers (OCT4 and NANOG) and early recurrence [27,28] and with sorafenib resistance properties in HCC [11,66]. In the current study, we found that the underlying mechanism of HCC sorafenib resistance involves a YAP-IGF-1R signaling loop that involves EMT-related proteins and YAP nuclear translocation in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 54%
“…However, the interplay between YAP and IGF signaling has remained uncertain in HCC sorafenib resistance. We previously illustrated that high expression of IGF-1R correlates with expression of cancer stemness markers (OCT4 and NANOG) and early recurrence [27,28] and with sorafenib resistance properties in HCC [11,66]. In the current study, we found that the underlying mechanism of HCC sorafenib resistance involves a YAP-IGF-1R signaling loop that involves EMT-related proteins and YAP nuclear translocation in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, there is a family of seven high-affinity IGF-binding proteins (IGFBP1 to IGFBP7), which bind and stabilize IGF and regulate its accessibility to its receptors [ 52 ]. Signaling through IGF1R plays an important role in tumorigenesis in the liver and is one of the hallmarks of HCC [ 53 , 54 ]. Over-activation of IGF signaling can be induced by increased levels of IGF1R or excessive IGF, which subsequently leads to prolonged activation of the MAPK/ERK signaling pathway [ 55 ].…”
Section: Mapk/erk Signaling Pathway In Hccmentioning
confidence: 99%
“…For this query, the knowledge graph also exhibits top ranked approved/investigative drugs that are targeting core genes associated with HCC (e.g., linsitinib, which is a selective inhibitor of insulin-like growth factor IGF-1R under investigation for the treatment of cancer and solid tumors). Since IGF-1R signaling is critical in tumor formation and activation of cancer stemness, which in turn may lead to tumor recurrence, this investigative drug has been reported in several clinical trials including prostate cancer, NSCLC, and advanced HCC [35].…”
Section: Hcc Query In Crossbar Web-servicementioning
confidence: 99%